2021
DOI: 10.1007/s11031-021-09897-z
|View full text |Cite
|
Sign up to set email alerts
|

The “Big Two” and socially induced emotions: Agency and communion jointly influence emotional contagion and emotional mimicry

Abstract: Three studies investigated the effects of two fundamental dimensions of social perception on emotional contagion (i.e., the transfer of emotions between people). Rooting our hypotheses in the Dual Perspective Model of Agency and Communion (Abele and Wojciszke in Adv Exp Soc Psychol 50:198–255, 10.1016/B978-0-12-800284-1.00004-7, 2014), we predicted that agency would strengthen the effects of communion on emotional contagion and emotional mimicry (a process often considered a key mechanism behind emotional cont… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 56 publications
(130 reference statements)
0
7
0
1
Order By: Relevance
“…Their research also suggested that “dispositionally empathic individuals exhibit the chameleon effect to a greater extent than do other people”. While the relation between the ability to automatically mimic others and empathise has been previously researched [ 14 , 15 , 16 , 17 ], there are no conclusive results on how to map one to the other, and the factors impacting the relation between the two. For example, Wrobel et al [ 17 ] and Peng et al [ 18 ] suggest that the mimicry response may be mediated by perceptions of the social meaning of the expressed emotion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their research also suggested that “dispositionally empathic individuals exhibit the chameleon effect to a greater extent than do other people”. While the relation between the ability to automatically mimic others and empathise has been previously researched [ 14 , 15 , 16 , 17 ], there are no conclusive results on how to map one to the other, and the factors impacting the relation between the two. For example, Wrobel et al [ 17 ] and Peng et al [ 18 ] suggest that the mimicry response may be mediated by perceptions of the social meaning of the expressed emotion.…”
Section: Introductionmentioning
confidence: 99%
“…While the relation between the ability to automatically mimic others and empathise has been previously researched [ 14 , 15 , 16 , 17 ], there are no conclusive results on how to map one to the other, and the factors impacting the relation between the two. For example, Wrobel et al [ 17 ] and Peng et al [ 18 ] suggest that the mimicry response may be mediated by perceptions of the social meaning of the expressed emotion. Both studies found that mimicry was present in relation to happiness, absent in perception of sadness, while Wrobel et al [ 17 ] identified a mixed pattern of response when anger was expressed.…”
Section: Introductionmentioning
confidence: 99%
“…Their research also suggested that "dispositionally empathic individuals exhibit the chameleon effect to a greater extent than do other people". While the relation between the ability to automatically mimic others and empathise has been previously researched [14][15][16][17], there are no conclusive results on how to map one to the other, and the factors impacting the relation between the two. For example, Wrobel et al [17] and Peng et al [18] suggest that the mimicry response may be mediated by perceptions of the social meaning of the expressed emotion.…”
Section: Introductionmentioning
confidence: 99%
“…While the relation between the ability to automatically mimic others and empathise has been previously researched [14][15][16][17], there are no conclusive results on how to map one to the other, and the factors impacting the relation between the two. For example, Wrobel et al [17] and Peng et al [18] suggest that the mimicry response may be mediated by perceptions of the social meaning of the expressed emotion. Both studies found that mimicry was present in relation to happiness, absent in perception of sadness, and Wrobel et al [17] identified a mixed pattern of response when anger was expressed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation